Development of a Thematic Mapping Learning Module for Social Studies Based on Geographic Information Systems - Somantri, Lili; Ihsan, Haikal Muhammad (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2025)
This study aims to develop a GIS-based thematic mapping learning module at the West Java Provincial Social Service. This study employed a Research and Development (R&D) method with the Dick and Carey model, which consists of 10 stages of processing and five categories, namely very good, good, moderate, less, and poor. The research variables used include usability aspects such as self-contained, stand-alone, adaptive, and user-friendly, as well as effectiveness, efficiency, learning appeal, and module quality elements like module format or framework. The software used in developing the module is the Quantum Geographic Information System (QGIS). The data analysis technique used to determine the feasibility of the module is a quantitative descriptive analysis technique. The data analyzed includes feasibility data with individual trials, small group trials, and field trials. Based on the results, it was found that the thematic mapping module on the social aspect based on GIS is included in the good to very good category, with a percentage value of 76% to 94%. The results of module development are very suitable for learning thematic mapping on the social aspect by utilizing GIS technology. Social data is usually very suitable to be presented in the form of choropleth maps or diagrams. Other thematic maps can be used, but they must be adjusted to the characteristics of the social data to be visualized.